Coexpression of organic anion‐transporting polypeptides 1B3 and multidrug‐resistant proteins 2 increases the enhancement effect of gadolinium‐ethoxybenzyl‐diethylenetriamine pentaacetic acid on hepatocellular carcinoma in magnetic resonance imaging. Issue 3 (7th May 2013) - Kimura, Yoshihide; Sato, Shinya; Hitomi, Eiichi; Ohyama, Makoto; Adachi, Kazunori; Inagaki, Yusuke; Yamakawa, Yoshihiro; Hirano, Atsuyuki; Kawai, Hiroki; Tsuchida, Kenji; Senoo, Kyouji; Katsumi, Kohei; et al.
<x xml:space="preserve">Abstract</x> Aim We aimed to elucidate the relationship between the contrast enhancement effect of gadolinium‐ethoxybenzyl‐diethylenetriamine pentaacetic acid (Gd‐EOB‐DTPA) on magnetic resonance imaging (MRI) of hepatocellular carcinomas (HCC) and the expressions of hepatocyte transporters (i.e. organic anion‐transporting polypeptide [OATP]1B3, multidrug‐resistant protein [MRP]2 and MRP3) and to clarify the characteristics of HCC with an MRI high‐contrast enhancement effect. Methods We retrospectively examined the relationship between the relative enhancement ratio (RER) of HCC, absolute and relative immunohistochemical staining scores of hepatocyte transporters, and histological differentiation of 22 HCC from 21 patients who had undergone preoperative Gd‐EOB‐DTPA‐enhanced MRI. Results RER had a significant correlation with OATP1B3 expression according to the absolute and relative scores (P = 0.016 vs 0.0006). The RER of HCC with high OATP1B3 and MRP2 expression levels was higher than that of HCC with low OATP1B3 or MRP2 expression levels (P = 0.0003). The RER of HCC with higher OATP1B3 rates was greater than that of HCC with lower OATP1B3 rates (P = 0.0005). HCC histological differentiation showed a significant correlation with OATP1B3 expression and RER (P = 0.023 vs 0.0095). Conclusion We found that coexpression of OATP1B3 and MRP2 influenced the high contrast enhancement of HCC on MRI.